Frequency of risk factors for cardiovascular disease among patients with acute coronary syndrome, Chiclayo - Hurtado Noblecilla, Emmanuel (2020)
Objective: To determine the frequency of risk factors for cardiovascular disease among patients with acute coronary syndrome (ACS) in two hospitals in Chiclayo. Methods: A cross-sectional study was carried-out among 100 admitted patients with ACS, a survey was applied to gather information on risk factors for cardiovascular disease. To evaluate symptoms associated with sleep-apnea we applied two scales, the Peruvian version of the Epworth somnolence scale and the snoring-somnolence scale. Results: the most frequent risk factors were abdominal obesity 87/88 (98.86%), age above 55 years in males and 65 years in females: 78/100 (78%), blood hypertension: 71/100 (71%), dyslipidemia: 54/97 (55.67%) and sedentarism: 49/97 (50.51%). Advanced age, blood hypertension, sedentarism and abdominal obesity were more common in females, while smoking was more common in males. Conclusions: The most frequent risk factor was abdominal obesity and the less frequent was family history of ACS.